2008
DOI: 10.1093/jhered/esm119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Connectivity in the Brooding Brittle Star Astrotoma agassizii across the Drake Passage in the Southern Ocean

Abstract: Studies examining population structure and genetic diversity of benthic marine invertebrates in the Southern Ocean have emerged in recent years. However, many taxonomic groups remain largely unstudied, echinoderms being one conspicuous example. The brittle star Astrotoma agassizii is distributed widely throughout Antarctica and southern South America. This species is a brooding echinoderm and therefore may have limited dispersal capacity. In order to determine the effect of hypothesized isolating barriers in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
128
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(140 citation statements)
references
References 63 publications
11
128
0
1
Order By: Relevance
“…Of these 264 species, 233 (88.3%) are endemic to Antarctic and/or Subantarctic waters (Munilla and Soler Membrives 2008). In the last decade, several molecular genetic studies in the marine Antarctic benthos provided strong evidence that Antarctic biodiversity is severely underestimated due to the presence of multiple morphologically highly similar lineages that most likely represent cryptic species (Allcock et al 1997;Held 2003;Held and Wägele 2005;Hunter and Halanych 2008;Leese and Held 2008;Linse et al 2007; Raupach and Wägele 2006;Raupach et al 2007;Thornhill et al 2008;Wilson et al 2007, Wilson et al 2009). A first study on the population structure of Nymphon australe, an Antarctic pycnogonid, for which a circumpolar distribution is assumed, revealed that several cryptic lineages co-occur in this taxon, which are likely to represent cryptic species .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 264 species, 233 (88.3%) are endemic to Antarctic and/or Subantarctic waters (Munilla and Soler Membrives 2008). In the last decade, several molecular genetic studies in the marine Antarctic benthos provided strong evidence that Antarctic biodiversity is severely underestimated due to the presence of multiple morphologically highly similar lineages that most likely represent cryptic species (Allcock et al 1997;Held 2003;Held and Wägele 2005;Hunter and Halanych 2008;Leese and Held 2008;Linse et al 2007; Raupach and Wägele 2006;Raupach et al 2007;Thornhill et al 2008;Wilson et al 2007, Wilson et al 2009). A first study on the population structure of Nymphon australe, an Antarctic pycnogonid, for which a circumpolar distribution is assumed, revealed that several cryptic lineages co-occur in this taxon, which are likely to represent cryptic species .…”
Section: Introductionmentioning
confidence: 99%
“…Lehmann et al 2007), however, the post-egg development of these specimens remains unknown. If no free-swimming larval stages exist, it should generally be expected that gene flow is reduced geographically and strong genetic differences according to an isolation-by-distance model are expected (but see Hunter and Halanych 2008 for a counter example). However, several pycnogonids are reported to have an eurybathic distribution (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Los niveles de divergencia estimados en Nacella son congruentes con datos moleculares recientes estimados en peces nototenoídeos (Stankovic et al 2002;Near et al 2012) y en distintos grupos de invertebrados marinos (Page & Linse, 2002;Wilson et al 2009) que muestran procesos más recientes de diversificación que los esperados por procesos de vicarianza asociada tectónica de placas. En este contexto, los niveles de distancias genéticas en Nacella son comparables a aquellos detectados entre linajes de Antártica y Sudamérica de los géneros Astrotoma (Hunter & Halanych, 2008), Odontaster (Janosik et al 2011), Sterechinus (Poulin et al 2014) y Yoldia (González-Wevar et al 2012a;Poulin et al 2014). Por lo tanto, el inicio de la divergencia entre provincias del Océano Austral no parece ser una consecuencia directa de los procesos de deriva continental ocurridos en la región sino que se encuentran asociados a procesos climáticos y oceanográficos más recientes ocurridos durante el Mio-Plioceno (Zachos et al 2001;Mackensen, 2004;Verducci et al 2009).…”
Section: Discussionunclassified
“…A number of studies on the phylogeography of marine invertebrates have been carried out at both sides of the Bass Strait that separates eastern from southern Australia (Waters and Roy 2003), the Bass Strait between South America and the Antarctic Peninsula (Hunter and Halanych 2008) and the Gibraltar Strait (Zulliger et al 2009), which is the only connection between the Atlantic Ocean and the Mediterranean Sea and measures less than 11 miles wide. In the case of the AtlantoMediterranean transition, the Almeria-Oran Front (AOF) located inside the Mediterranean has been defined as the main boundary between Atlantic and Mediterranean surface waters, but the transition at the biological level still remains controversial (Borsa et al 1997;Cimmaruta et al 2005;Patarnello et al 2007) and marine species display different patterns of genetic structure at both sides of this particular area (e.g.…”
Section: Introductionmentioning
confidence: 99%